Asymmetric Guerbet Reaction to Access Chiral Alcohols. Issue 28 (18th May 2020) - Wang, Kun; Zhang, Lin; Tang, Weijun; Sun, Huaming; Xue, Dong; Lei, Ming; Xiao, Jianliang; Wang, Chao
Abstract: The first example of an asymmetric Guerbet reaction has been developed. Using commercially available, classic Noyori Ru II ‐diamine‐diphosphine catalysts, well‐known in asymmetric hydrogenation, racemic secondary alcohols are shown to couple with primary alcohols in the presence of a base, affording new chiral alcohols with enantiomeric ratios of up to 99:1. Requiring no reducing agents, the protocol provides an easy, alternative route for the synthesis of chiral alcohols. Mechanistic studies reveal that the reaction proceeds via a Ru‐catalyzed asymmetric hydrogen autotransfer process in concert with a base‐promoted allylic alcohol isomerization. Abstract : Commercially available, classic Noyori Ru II ‐diamine‐diphosphine catalysts catalyze the cross coupling of racemic secondary alcohols with primary alcohols in the presence of a base, affording new chiral alcohols with enantiomeric ratios of up to 99:1.